2019
DOI: 10.3389/fphar.2019.01366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mediterranean Diet Enriched in High Quality Extra Virgin Olive Oil on Oxidative Stress, Inflammation and Gut Microbiota in Obese and Normal Weight Adult Subjects

Abstract: Introduction: The Mediterranean Diet (MD) is useful in the prevention of overweight, obesity and metabolic disease. High Quality-Extra Virgin Olive Oil (HQ-EVOO), an essential component of this diet, exerts protective effects against chronic diseases. Gut Microbiota (GM), recognized as a key factor in driving metabolic activities, is involved in the regulation of host immunity. Lactic Acid Bacteria (LAB) and their probio-active cellular substances produce beneficial effects in the gastrointestinal tract.Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(129 citation statements)
references
References 44 publications
5
116
0
Order By: Relevance
“…Nevertheless, at the genus level, several important differences were highlighted in our sample. In particular, as previously reported, the Streptococcus genus was highly abundant among overweight/obese participants, so as the Dorea and Dialister, which were also mainly represented among low-active individuals [37,38]. Interestingly, Dorea and Dialister were found to be related with insulin secretion and fasting blood glucose, suggesting their role in type 2 diabetes development in overweight-obese individuals [38].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Nevertheless, at the genus level, several important differences were highlighted in our sample. In particular, as previously reported, the Streptococcus genus was highly abundant among overweight/obese participants, so as the Dorea and Dialister, which were also mainly represented among low-active individuals [37,38]. Interestingly, Dorea and Dialister were found to be related with insulin secretion and fasting blood glucose, suggesting their role in type 2 diabetes development in overweight-obese individuals [38].…”
Section: Discussionsupporting
confidence: 65%
“…Lachnospira was more represented among individuals with higher adherence to the MD, while Paraprevotella was more represented in those with lower MD scores. The literature reports that vegetable-based diets tend to correlate with the amount of short-chain fatty acids (SCFA), which are produced by gut bacteria through dietary fiber fermentation and have fundamental effects on the immunity, metabolism, and inflammation processes of the host [38]. Lachnospira among Firmicutes, so as Prevotella among Bacteroidetes, seem to be involved in the fermentation of fibers, leading to a higher SCFA production.…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the main distinctive components of the MD is EVOO, representing the main source of dietary fat and polyphenols [ 31 , 32 ], the latter being potent inhibitors of reactive oxygen species and associated with a reduced risk for CVD and several types of cancer [ 2 , 33 , 34 , 35 , 36 ]. Several studies confirmed the beneficial effects of polyphenols in olive oil on heart disease risk factors and oxidative damage [ 37 , 38 , 39 , 40 ]. In addition, EVOO has been widely studied for its favorable effects on plasma concentrations of low-density lipoprotein cholesterol (LDL-C) and total cholesterol [ 33 , 39 , 41 , 42 , 43 ], as well as on blood pressure [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, a preclinical study has shown that an EVOO-enriched diet had the best results on the musculoskeletal system in an osteoarthritis rat model, including decreased IL-6 expression [ 65 ]. On the other hand, an MD rich in high quality EVOO also significantly increases IL-10 levels [ 40 ]. By correlation analysis, we interestingly found an inverse association between changes in IL-6 and those in SFT max, which further highlights the concurrent effects of olive oil supplementation on anti-inflammatory cytokines and abdominal fat distribution.…”
Section: Discussionmentioning
confidence: 99%
“…EVOO has been widely studied because of its effects in preventing several metabolic diseases and pathologies, such as atherosclerosis, cardiovascular diseases, serum lipoprotein levels, oxidative stress, obesity, type 2 diabetes, inflammation and cancer [1][2][3][4][5]. Overall, the health-promoting effects of EVOO are mainly related to its inherent chemical composition, such as the fatty acid profile [6] rather than other "minor" components (nearly 2% of the total weight).…”
Section: Introductionmentioning
confidence: 99%